PENGARUH PEMBERIAN HASIL FERMENTASI KULIT PISANG SEBAGAI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN TANAMAN MAWAR (Rosasp.) - Noverensi Noverensi; Husna Yetti; Arnis En Yulia2 (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to see the effect of banana peel fermentation as liquid organic fertilizer on the growth of rose plants and determine the best dosage for the growth of rose plants. This research was conducted at the Faculty of Agriculture, University of Riau's experiment station from August to November 2017. This research was conducted in the form of an experiment using a non-factorial complete randomized design consisting of 5 levels and 3 replications. Fermented banana peel as a liquid organic fertilizer consists of 0, 150, 300, 450, 600 ml per polybag. The parameters observed were the number of shoots, length of shoots, number of leaves, when the first flower appeared and the number of blooms. The results showed that administration of banana peel fermented as a liquid organic fertilizer significantly affected the number of shoots, number of leaves, when the first flower appeared and the number of flowers. Provision of banana peel  fermentation as a liquid organic fertilizer with a dose of 450 ml per polybag gives the highest yield for the growth of rose plants.Keywords : Rose, liquid organic fertilizers, dosage